Impact of Price-Responsive Load and Renewables in an Emission-Aware Power Systems - Boming Liu; Jin Dong; Byungkwon Park; Jianming Lian; Teja Kuruganti (IEEE Open Access Journal of Power and Energy)
Decarbonization of the power grid will require collective efforts from different entities. As the global energy sector shifts from fossil-based systems of energy production to renewable energy sources to reduce energy-related greenhouse gas emissions, demand-side flexibility can play an important role in decarbonizing the grid. In this paper, we explore the impact of price-responsive loads and renewable resources in an emission-aware power system. The proposed simulation framework utilizes a modified optimal power flow formulation that considers the carbon cost in addition to the fuel cost of generations. The system also incorporates the demand flexibility through market coordination based on the emission-aware locational marginal prices (E-LMPs) to contribute to the overall emissions reduction. Numerical studies on the test system were performed to compare the emission-aware power system operation and the traditional power system operation in different scenarios. Quantitative results on carbon emission reduction are provided to evaluate the impact of the price-responsive loads and renewable resources. The results demonstrate that E-LMPs and the active participation of flexible loads can help reduce carbon emissions, especially with renewable resources in the system.